Facile Synthesis and Application of Ag-NPs for Controlling Antibiotic-ResistantPseudomonas spp. and Bacillus spp. in a Poultry Farm Environment - Aminur Rahman; Harunur Rasid; Md. Isahak Ali; Nymul Yeachin; Md. Shahin Alam; Khandker Saadat Hossain; Md. Abdul Kafi (Journal of Nanotechnology)
This study synthesized silver nanoparticles (Ag-NPs) using silver nitrate (AgNO3) as the ion source and sodium tripolyphosphate (STPP) as reducing as well as capping agents. The synthesized Ag-NPs were confirmed initially using Ag-NPs specific λmax at 410 nm with UV-Vis spectrophotometry and homogenously distributed, 100–300 nm size, and round-shaped particles were realized through atomic force microscopy (AFM) and transmission electron microscopy (TEM) image analysis. The various reaction condition-based studies revealed 0.01 M AgNO3 yields maximum particle after 4 h reduction with 1% STPP. Bacillus spp. (n = 23/90) and Pseudomonas spp. (n = 26/90) were isolated from three different poultry farms for evaluating the antibacterial activity of Ag-NPs. Among the PCR confirmed isolates, 52% (12/23) Bacillus spp. were resistant to ten antibiotics and 65% (17/26) Pseudomonas spp. were resistant to eleven antibiotics. The representative resistant isolates were subjected to antibacterial evaluation of synthesized Ag-NPs following the well diffusion method, revealing the maximum sensitive zone of inhibition 19 ± 0.2 mm against Bacillus spp. and 17 ± 0.38 mm against Pseudomonas spp. The minimum inhibitory concentration (MIC) and minimum bacterial concentration (MBC) of Ag-NPs were 2.1 μg/ml and 8.4 μg/ml, respectively, for broad-spectrum application. Finally, the biocompatibility was determined by observing the viability of Ag-NP-treated BHK-21 cell through trypan blue-based exclusion assay revealing nonsignificant decreased of cell viability ≤2MIC doses. Thus, the synthesized Ag-NPs were proven as biocompatible and sensitive to both Gram-positive and Gram-negative bacteria of the poultry farm environmental samples.